Parsing the Popular: A Communicative Action Approach to Folklore - Laba, Martin (Ethnologies)

(untitled) (Association Canadienne d'Ethnologie et de Folklore, 2008)
This work argues for an engagement with, and analysis of folkloric expression through the concept and cultural practices of communicative action. The article is motivated by a critical need to situate folklore within dynamic and compelling currents of popular culture. It is suggested that the capacities of folklore as popular culture serve to renew and impel folklore studies for traction and relevance in analytic encounters with contemporary media, culture, and society. Foundational concepts and theoretical trajectories in folklore and communication are detailed, challenged and revised with a view to capturing the substance and significance of folklore in cultural terms. The analysis presented is premised on the notion that there is a decisive intersection of the concepts and practices of folklore and popular culture to the extent that definitional boundaries between them are imprecise and unsustainable. The analysis explores how folklore as popular culture socially articulates, negotiates and asserts meaning in codes, practices, knowledge, spaces and expressive strategies in contemporary cultural conditions and environments.